Listening to China’s Cultural Revolution: Music, Politics, and Cultural Continuities - Clark, Paul; Pang, Laikwan; Tsai, Tsan-Huang (Palgrave Macmillan US, 2016)
Bringing together the most recent research on the Cultural Revolution in China, musicologists, historians, literary scholars, and others discuss the music and its political implications. Combined, these chapters, paint a vibrant picture of the long-lasting impact that the musical revolution had on ordinary citizens, as well as political leaders.
Includes bibliographical references and index
Keywords: Musik; Kulturrevolution